1972
DOI: 10.1002/aja.1001350302
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in mitotic activity and 3H‐thymidine uptake in the duodenum: Effect of isoproterenol on the mitotic rhythm

Abstract: Mitotic activity in the duodenum of the rat and mouse exhibits a circadian periodicity with a peak in the rat between 1200 and 1500 hours and a sustained trough between 1800 and 0600. Scintillation counts revealed a similar rhythm in the total uptake of 3H-thymidine by the rat duodenum with a sustained but fluctuating crest occurring between 0800 and 1800 and a trough between 1900 and 0100. In the mouse the peak mitotic activity occurred at 0900 and the trough at 1700. Isoproterenol completely abolishes the rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…In the corneal epithelium it has been shown that a steady rate of mitosis is maintained from 10 to 14 days after birth when comparing values at 07.00 and 19.00 h on each of these days (10). At the onset of the 3rd week after birth (day 15) a circadian rhythm is initiated with a peak at 07.00 and a trough at 19.00 h. This rhythm is almost identical to that which occurs in adult mice (4,21) and rats (8,22) that the rhythm which begins at 15 days is maintained into adulthood.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…In the corneal epithelium it has been shown that a steady rate of mitosis is maintained from 10 to 14 days after birth when comparing values at 07.00 and 19.00 h on each of these days (10). At the onset of the 3rd week after birth (day 15) a circadian rhythm is initiated with a peak at 07.00 and a trough at 19.00 h. This rhythm is almost identical to that which occurs in adult mice (4,21) and rats (8,22) that the rhythm which begins at 15 days is maintained into adulthood.…”
mentioning
confidence: 69%
“…In 8-day-old rats (---------) differences between the highest and lowest mitotic index are not statistically significant. eral studies have indicated that 3H-TdR uptake and mitotic rate curves have similar phasing and may even be superimposed in many cases (21,23). The circadian rhythm of acinar cell mitoses is, however, quite different in phasing from the pattern of variation in gland weight and secre tory protein which reaches a maximum in the early evening (17.00 h) prior to the nocturnal feeding period, with a decrease of 53% by 05.00h.…”
Section: Parotid Gland Acinar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tritiated thymidine for the labeling of the DNA-synthetizing cells and for the determination of the phases in the cell cycle demonstrated a nocturnal increase of the percentage of labeled cells during night in fasting mice [24], A simultaneous increase of the percentage of mitosis was observed [22], The photoreversibility of this rhythm suggested the circadian origin of the varia tion [23], The simultaneous increase of LI and MI was explained by two events: a nocturnal increase in the number of proliferative cells [11] and a shorter duration of the cell cycle time during the night with a shortening of G1 and G2 phases [24], In fed rats, circadian rhythms in mitotic activity and 3H-thymidine uptake were observed [21,26] with conflicting results. Scheving et al [21] found a diurnal peak for LI and MI between 11.00 a.m. and 4.00 p. m., whereas T utton [26] calculated a shorter cell cycle time during the night and obtained a maximal MI between 6.00 a.m. and 10.00 a.m.…”
Section: Discussionmentioning
confidence: 99%
“…Four groups received injections of IPR, as described above, between 9 a.m. and 10 a.m. so as to minimize any effect of IPR on the circadian rhythm of DNA synthesis (Burns and Scheving, 1973; Scheving, Burns and Pauly, 1972). After an interval of 8, 28 or 31 h, 3 of these groups were given 77 mg MNU/kg (LD50 > 90 mg/kg) by i.v.…”
mentioning
confidence: 99%